The Fédération Internationale de l’Automobile Strategy Towards Sustainable Development through Formula E in A Social Purpose Perspective - Fenanda Almira Rasyid; Januari Pratama Nurratri Trisnaningtyas (International Journal Of Economics Social And Technology, 2026)
The Fédération Internationale de l’Automobile (FIA) utilizes the Formula E championship as a global sustainability platform in motorsports. This study aims to explain FIA's operational and advocacy strategies in supporting sustainable development through this event from 2014 to 2024. Using a descriptive qualitative method with a literature review approach, secondary data were analyzed based on the Social Purpose of NGO framework. The findings indicate that the FIA fully operates as a hybrid NGO to achieve its social purpose. Through its operational strategy, the FIA implements sustainable technological innovations and green event management. Concurrently, its advocacy strategy utilizes insider approaches via strategic international partnerships and outsider approaches through mass public awareness campaigns. Together, these integrated strategies concretely contribute to the three main pillars of sustainable development: economic, social, and environmental. The novelty of this study lies in its comprehensive analysis of the Formula E ecosystem as an instrument for systemic clean energy transition, moving beyond previous studies that merely focused on single emission reduction targets in Formula 1. Furthermore, this research contributes scientifically by enriching International Relations and sustainability governance literature, demonstrating how transnational sports organizations possess significant diplomatic and social engineering capabilities to drive global climate action.